FORMULATION OF BAR SHAMPOO BASED ON Eucheuma cottonii SEAWEED EXTRACT WITH VARYING CONCENTRATIONS OF SODIUM COCOYL ISETHIONATE - Hidayana, Acut Rahmatul; Ridwan, R; Wijaya, Nanang Rahmat (Jurnal Sains dan Teknologi Reaksi, 2025)
This study aims to formulate shampoo bars as an environmentally friendly alternative hair care product by utilizing nutrient-rich Eucheuma cottonii seaweed extract and varying the concentration of Sodium Cocoyl Isethionate (SCI) as a natural surfactant that does not irritate the scalp. The E. cottonii extract was obtained through maceration with 96% ethanol and concentrated using a rotary vacuum evaporator. The SCI concentrations used were 30%, 35%, 40%, 45%, and 50%, while the E. cottonii extract concentrations were 2%, 6%, 10%, 14%, and 18%. The physical quality of the shampoo bar was evaluated through acidity (pH) testing, moisture content, foam stability, organoleptic testing (color, aroma, texture), and irritation testing. The results showed that all formulations had a pH of 5.5–6.33, meeting SNI 06-2692-1992 standards. The highest moisture content was recorded at 16.96% in SCI 30% and 18% extract, while the lowest was 5.26% in SCI 50% and 2% extract. Foam stability increased with increasing SCI, with the highest foam stability percentage of 79.22% in SCI 50% and 2% exract. Organoleptic testing showed good acceptance of color and texture, with the aroma of some formulas slightly changing to be less fresh, but generally still acceptable to the panelists. Irritation testing on 25 panelists did not show any serious irritation, indicating the optimal quality of the shampoo bar produced.  Keywords: Eucheuma cottonii, Maceration, Physical Quality, Shampoo bar, Sodium Cocoyl Isethionate